Psycho-linguistic and socio-cultural approaches to language learning: a never ending debate - Cardenas Claros, Monica Stella (Colombian Applied Linguistics Journal, 2008)
This paper critically examines psycholinguistic and socio-cultural approaches for language learning. It provides a thorough discussion of the ontological positions where they originate, the methods they use, some relevant work under each perspective and most importantly criticisms that each perspective faces. The paper concludes that no approach is better than the other and advocates for collaboration projects nurtured from both perspectives.